Investigations on the Particle Fouling and Backwash Efficiency During Microplastic Microfiltration–Particle Size Aspects - Saremi, Saeedeh; Scheer, Leonie Marie; Braun, Gerhard; Koch, Marcus; Gallei, Markus; Faust, Matthias (Membranes (Basel), 2025)
The characteristics of polystyrene (PS) microplastic (MP) microfiltration by a cellulose acetate (CA) membrane were investigated within this study. Particle sizes and pore sizes were selected in a comparable range in order to challenge the dead-end microfiltration. Backwashing experiments round up the investigations. Microfiltration characteristics and particle size measurements, as well as a particle fouling analysis by different methods, were applied in the study in order to provide a comprehensive picture of particle deposition and particle fouling structuring. The particle removal efficiency was particle-size-dependent, and especially small particles were further reduced during the proceeding filtration, while the larger particles were already removed within the first minutes of filtration. This observation was attributed to the pore blocking (internal and/or complete) and build-up of the filter cake. The difference in the particle-fouling structure at low and elevated filtration pressure significantly influences the backwashing efficiency. The particle fouling resulting from low-pressure filtration was completely removed due to the backwashing procedure applied, while an increased filtration pressure resulted in a different particle-fouling structure, which negatively influenced the backwashing efficiency. This knowledge of the formation and structure of the MP particle fouling and its removal by backwashing is a prerequisite for further process development.